2011
DOI: 10.1111/j.1468-3083.2011.04076.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of severity of the cutaneous manifestations and age on the prevalence of several cardiovascular risk factors in patients with psoriasis

Abstract: There was strong evidence that psoriasis patients have an increased cardiovascular risk, chiefly those over the age of 40 years, probably because of the chronic inflammatory state. It seems that the severity of the cutaneous manifestations was not associated with a higher risk in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
37
3
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 30 publications
8
37
3
2
Order By: Relevance
“…This OR was higher than that reported in the Israeli population but much lower than that reported in the Indian population (OR of 6.09) . The association between psoriasis and MBS has been attributed to inflammatory markers shared by both psoriasis and MBS, such as Th1 cytokines (TNF‐ α ), CRP, and IL‐6 . Furthermore, IL‐17 is involved in the pathogenesis of psoriasis and is elevated in patients with unstable coronary arterial disease .…”
Section: Discussionmentioning
confidence: 63%
“…This OR was higher than that reported in the Israeli population but much lower than that reported in the Indian population (OR of 6.09) . The association between psoriasis and MBS has been attributed to inflammatory markers shared by both psoriasis and MBS, such as Th1 cytokines (TNF‐ α ), CRP, and IL‐6 . Furthermore, IL‐17 is involved in the pathogenesis of psoriasis and is elevated in patients with unstable coronary arterial disease .…”
Section: Discussionmentioning
confidence: 63%
“…Furthermore, we also found that associations with all variables of MBS were significantly linked with disease severity except for abdominal obesity. In an earlier report, Rosa et al . found that parameters of MBS were not related to psoriasis severity.…”
Section: Discussionmentioning
confidence: 99%
“…It affects nearly 3% of the global population, including 125 million people worldwide [3]. Although the pathogenesis of psoriasis is still not fully understood, increased oxidative stress, endothelial dysfunction, and systemic inflammatory response are considered as the most important mechanisms in the development of the disease, as is the case in most cardiovascular diseases [4]. Patients with psoriasis have excess risk of atherosclerotic vasculopathies such as coronary artery disease, hypertension, metabolic syndrome, obesity, and diabetes mellitus [57].…”
Section: Introductionmentioning
confidence: 99%